A comparison of seven academic and nonacademic urban food system resilience assessment frameworks - Walker, Kara E.; Jenkins, Tricia; Kohn, Dustin R.; Stuteville, Rebekkah; Pliakoni, Eleni D.; Brenes, Priscilla (Frontiers in Sustainable Food Systems, 2025)
Diverse food system resilience frameworks and assessment tools are being developed to measure food system performance in the face of disruptive events. The divide between academic research and gray literature can result in inaccessibility of assessment tools to communities and non-academic researchers. The authors performed a literature review and selected seven urban food system resilience assessment frameworks for comparison with resilience attributes, as well as consideration of their intended audience; spatial scope; data type; data collection; strengths; and ease of use. The frameworks were found to match between three and seven of the ten identified resilience attributes, with a range of intended audiences. Framework data collection methodologies included surveys, spatial data analysis, and mixed methods approaches to collect quantitative, semi-quantitative, and qualitative data. Most of the included frameworks include flexible indicators and metrics for investigators to collect relevant data for their planning goals. While the ability to develop unique metrics can be a strength, undefined metrics present an issue for non-academic researchers in communities seeking to effectively assess their own food system. Limitations in existing assessment tools include a wide range of intended outcomes and burdensome data collection. The comparison of the assessment tools resulted in recommendations of frameworks for academic and non-academic researchers and revealed gaps including a lack of fair labor considerations. This review allows researchers to develop effective frameworks for diverse users to prioritize resilience in food systems.